Implementation of Islamic Education Takhasus Class Program Policy in Senior High School - Fatimah, Fatimah; Dewi, Nefira; Nuraiman, Nuraiman (Institute of Research and Community Service STAI Yayasan Tarbiyah Islamiyah Kota Padang, 2023)
The public's views and interest in madrasas are still low and competition between madrasas is high, so the head of the madrasah and the administrators of Madrasah Aliyah Padang State consulted to find a way to make the madrasah attractive to many people, and made a policy by holding a superior class program called the class program. Takhashus, which started to be implemented in the 2017/2018 academic year until now, has become a special attraction for the community, causing the number of students to increase every year. This research aims to analyze whether students actually have self-concept and self-awareness in applying discipline in learning. This research uses qualitative methods. The type of research is descriptive, and data collection techniques are through observation, interviews, and document study at Madrasah Aliyah Negeri 3 Padang. The results of the analysis show that student recruitment in the implementation of the Takhasus class program has started since the registration of new students by carrying out academic tests, interview tests, verse memorization tests, and filling out permission letters from parents for students to be quarantined for 4 days at the training camp. The methods that can be used in this training are the discussion method, demonstration method, memorizing the Koran, and lecture method. The results of this research can be used as initial data for future researchers in studying this problem in different contexts and issues.